Internalisasi Nilai-Nilai Islam Nusantara Melalui Mata Pelajaran Aqidah Akhlak - Rizal, Syaiful (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Ilmiah (LP3M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2023)
Islamic Nusantara values ​​become real behavior, students need to be given an understanding of Islamic Nusantara values ​​from an early age as an effort to increase their awareness so that they can appreciate the diversity that exists so that in the end they can behave in a humanist, pluralist and democratic manner. As well as being a process of cultivating a way of life that respects, is sincere, and is tolerant of cultural diversity that lives in the midst of a plural society. It is hoped that by instilling the values ​​of Nusantara Islam in education, there will be resilience and flexibility in the nation's mentality in facing social conflicts, so that national unity will not be easily broken and cracked. The focus of this research is how to internalize the values ​​of Tawazun, Tawasyuth and I'tidal values ​​in the Aqidah Akhlak Subject at MTs Tanah Wulan? The approach used is to use a qualitative type approach. The results of this study show that: 1). The application of Tawazun Values ​​uses habituation, this application is carried out at school and outside the school (community). This habituation is applied in the hope that all students can instill and apply it in the community environment later. Meanwhile, the Tawazun method uses lecturing and discussion methods. 2). The application of Tawassuth Values ​​is also the same as habituation, this habituation is always applied by all teachers at school and in the community, while the method used is lecture and discussion methods. 3). the application of I'tidal values ​​is also by habituation, while the methods used in applying I'tidal values ​​are using discussion and lecture methods. As for habituation before entering class, students are required to carry out Duha prayer and read short letters, Punishment or punishment given to students who play games when carrying out the habituation of Duha prayer and read short letters to repeat them again, while the punishment for students who do not following the dluha prayer students are punished by standing in front of the mushollah by reading the Waqi'ah letter. Keywords: Values, Archipelago Islam, Aqidah Akhlaq